MECP2 mutations in Malaysian Rett syndrome patients - Fong, C.B.; Thong, M.K.; Sam, C.K.; Mohamed Noor, M.N.; Ariffin, R. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
Through the use of post-PCR high-performance liquid chromatography, 65 percent of 20 RS patients were found to have mutation(s) in the MECP2.